Coupled Systems with Hyperchaos and Quasiperiodicity - Kuznetsov, A.P.; Sedova, Yu.V. (Journal of Applied Nonlinear Dynamics, 2026)
A model with hyperchaos is studied by means of Lyapunov twoparameter analysis. The regions of chaos and hyperchaos, as well as autonomous quasiperiodicity are identified. We discuss the picture of domains of different regimes in the parameter plane of coupled systems, corresponding to the cases of interaction of quasiperiodic and hyperchaotic subsystems.